Feedback control of dynamic systems - Franklin, Gene F. (Pearson Education Limited, 2015)
Feedback Control of Dynamic Systems covers the material that every engineer, and most scientists and prospective managers, needs to know about feedback control–including concepts like stability, tracking, and robustness. Each chapter presents the fundamentals along with comprehensive, worked-out examples, all within a real-world context and with historical background information. The authors also provide case studies with close integration of MATLAB throughout.